Formulasi dan Analisa Kandungan Zat Gizi pada Formulasi Puding Sedot - Ningsih, Windi Indah Fajar; Ramdika, Sari Bema; Harwanto, Fatria (HB PRESS, 2024)
Product modification can be used as an intervention method to prevent nutritional problems. The addition of ingredients that have certain nutrients can be used in the modification process, thereby increasing the product's superiority and affecting the quality of the resulting product. It is necessary to analyze the nutrient content to decide whether the nutrients in the product are convenient with the specified nutritional adequacy claim. The purpose of this study was formulating suction puding made from high protein ingredients and analyzing the nutrient content. This research was a quantitative study included in the experimental design to determine the nutritional content of moisture, ash, fat, protein, and carbohydrate content in the formulation of suction puding. Formulation was carried out in dietetic and culinary laboratory and Analysis of nutrient content was carried out at the Laboratory of Chemistry and Microbiology of Agricultural Products, Department of Agricultural Technology, Faculty of Agriculture, Sriwijaya University. Data analysis in this study is bivariate using ANOVA test if the data is normally distributed and Duncan's further test, while data that is not normally distributed uses Kruskall-Wallis test and Mann-Withney further test. The results was formulation samples consisted of four different recipes of suction puding formulations (A, B, C and D) then the bivariate analysis in this study showed significant differences in water, fat, protein, and carbohydrate content (p<0.05), while in ash content there was no significant difference in the various formulations (p>0.05).